Correction: Almuhanna et al. Antibacterial, Antibiofilm, and Wound Healing Activities of Rutin and Quercetin and Their Interaction with Gentamicin on Excision Wounds in Diabetic Mice. Biology 2024, 13, 676 - Yasir Almuhanna; Abdulrahman Alshalani; Hamood AlSudais; Fuad Alanazi; Mohammed Alissa; Mohammed Asad; Babu Joseph (Biology)
In the original publication [...]